PENGENALAN SOFTWARE AUTOCAD UNTUK KEPERLUAN DESAIN PADA SISWA SMKI RAUDLATUL HUSNA - Ni Made Seniari; Supriyatna Supriyatna; Bagus Widhi Dharma; Abdul Natsir; Ida Ayu Sri Adnyani; Sabar Nababan; I Made Ginarsa (Jurnal Abdi Insani, 2022)
Raudathul Husna Islamic Vocational School located in Mertak Tombok village, Praya, Central Lombok was established in 2020, with a total of 57 students. Has one major, namely Visual Communication Design (DKV). Core subjects according to the curriculum include Creative Products and Entrepreneurship (PKWU), publication design and computer graphics. For this reason, students need to be given additional knowledge, namely the introduction of AutoCAD software which is not included in the curriculum. The aim is to support and complete students' knowledge and skills in a broader and more general design. Students are expected to be able to make a site plan for a yard and design a simple house plan. The method used is to give an introduction to the basics of Autocad software from module one to module 4. Each module discusses skills in operating and applying in the form of a design step by step. Simultaneously given lectures, students practice in groups from each stage of the module. Of the thirty-five students who were divided into 7 groups, four groups were able to practice up to module 3. Three groups were only able to practice up to module 2. None of the students had been able to practice up to module 4 proficiently. However, with intensive assistance from the PKM team, 2 groups can make site plans and simple house plans. The introduction of AutoCad software at SMKi was welcomed by the school. Students feel great benefits from the implementation of this activity, it is useful to open insight, experience and increase student skills by 80.28%